The legal construction of personal work relations - Freedland, Mark; Kountouris, Nicola (New York, 2011)
"This book explores the conceptual framework of European employment law, focusing on understanding the law's construction of employment relationships. The book draws on extensive comparative research of the legal architecture of employment relations in national legal systems and EU law to analyse the traditional model of the contract of employment and the difficulties of using the traditional model to frame modern working relationships.